Design, synthesis, and evaluation of novel inhibitors for wild-type human serine racemase. Issue 3 (1st February 2018) - Takahara, Satoyuki; Nakagawa, Kiyomi; Uchiyama, Tsugumi; Yoshida, Tomoyuki; Matsumoto, Kazunori; Kawasumi, Yasuo; Mizuguchi, Mineyuki; Obita, Takayuki; Watanabe, Yurie; Hayakawa, Daichi; Gouda, Hiroaki; Mori, Hisashi; et al.
Graphical abstract: Abstract: Most of the endogenous freed -serine (about 90%) in the brain is produced by serine racemase (SR).d -Serine in the brain is involved in neurodegenerative disorders and epileptic states as an endogenous co-agonist of the NMDA-type glutamate receptor. Thus, SR inhibitors are expected to be novel therapeutic candidates for the treatment of these disorders. In this study, we solved the crystal structure of wild-type SR, and tried to identify a new inhibitor of SR by in silico screening using the structural information. As a result, we identified two hit compounds by their in vitro evaluations using wild-type SR. Based on the structure of the more potent hit compound1, we synthesized 15 derivatives and evaluated their inhibitory activities against wild-type SR. Among them, the compound9C showed relatively high inhibitory potency for wild-type SR. Compound9C was a more potent inhibitor than compound24, which was synthesized by our group based upon the structural information of the mutant-type SR.